ANALISIS FAKTOR KESULITAN GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) DI SDN 05 AMPENAN - Miftahul Jannah; Nurul Kemala Dewi; Itsna Oktaviyanti (Program Studi PGSD, FKIP, Universitas Mataram, 2021)
This study aims to describe the difficulty factors of teachers in compiling a lesson plan (RPP) at SDN 05 Ampenan. The approach used is a qualitative approach with narrative descriptive research type. Data collection techniques using interviews and documentation. Data analysis using data analysis Model Milles and Huberman which consists of, data reduction, data presentation, and drawing conclusions. The results showed that the difficulties experienced by the teacher in compiling and developing several components of the lesson plans were: (1) formulating indicators of competency achievement, (2) determining learning models and methods, (3) determining learning media and (4) assessing. Some of these difficulties are influenced by several factors, including: (1) teachers 'understanding in preparing lesson plans, (2) teachers' ability to use IT, (3) time availability, (4) student characteristics.